Paul and the language of faith - Gupta, Nijay K. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2020)
"This book will root Paul's love language in its context in the ancient world, where love was seen as affection, loyalty, and generosity; Paul's use is remarkable in making the emphasis one where love is understood as generosity and this, in a culture of reciprocity and mutual expectation"--
Includes bibliographical references (pages 193-215) and indexes.
Keywords: Bible. -- Theology; Pistis (The Greek word); Faith -- Biblical teaching..